2017
DOI: 10.1101/136564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated time course omics analysis distinguishes immediate therapeutic response from acquired resistance

Abstract: BACKGROUND: Targeted therapies specifically act by blocking the activity of proteins that are encoded by genes critical for tumorigenesis. However, most cancers acquire resistance and long-term disease remission is rarely observed. Understanding the time course of molecular changes responsible for the development of acquired resistance could enable optimization of patients' treatment options. Clinically, acquired therapeutic resistance can only be studied at a single time point in resistant tumors. To determin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Analysis of ADCCS1 and ADCCR1 cells from challenges 30 to 35 was performed with the CoGAPS algorithm (9), using the timecourse analysis pipeline from Stein-O'Brien and colleagues (18). The PatternMarker statistic for CoGAPS (10) identified 300 genes with consistent upregulation and 450 genes with consistent downregulation in ADCCR1 cells compared with ADCCS1 cells across all challenges.…”
Section: Overexpression Of Interferon-and Histone-associated Genes Inmentioning
confidence: 99%
“…Analysis of ADCCS1 and ADCCR1 cells from challenges 30 to 35 was performed with the CoGAPS algorithm (9), using the timecourse analysis pipeline from Stein-O'Brien and colleagues (18). The PatternMarker statistic for CoGAPS (10) identified 300 genes with consistent upregulation and 450 genes with consistent downregulation in ADCCR1 cells compared with ADCCS1 cells across all challenges.…”
Section: Overexpression Of Interferon-and Histone-associated Genes Inmentioning
confidence: 99%
“…In another study, we have shown that while SCC25 acquires cetuximab resistance due to chronic exposure, 44 the transcriptional changes occur a few weeks prior to the promoter hyper-or hypomethylation, with the latter being detected when cells are already resistant. Here, we investigated the hypothesis that some of the genes involved in resistance are controlled by chromatin remodelling that occurs prior to methylation, while the cells are still sensitive to the therapy, and drive a proportion of the expression changes.…”
Section: Discussionmentioning
confidence: 96%
“…This algorithm was applied to the gene expression time-course data of ASC stimulated with TEC-EV. CoGAPS was previously used to successfully delineate the time-course data of therapeutic response in breast and HNSCC (Hill et al, 2016;Stein-O'Brien et al, 2018). In our case, it detected the critical role of inflammatory response gene set to respond to TEC-EV stimuli within 24 h (Figure 4).…”
Section: Discussionmentioning
confidence: 79%